The Role of Glucocorticoid Receptor and Oxytocin Receptor in the Septic Heart in a Clinically Relevant, Resuscitated Porcine Model With Underlying Atherosclerosis - Merz, Tamara; Denoix, Nicole; Wigger, Daniela; Waller, Christiane; Wepler, Martin; Vettorazzi, Sabine; Tuckermann, Jan; Radermacher, Peter; McCook, Oscar (Frontiers in Endocrinology, 2020)
The pathophysiology of sepsis-induced myocardial dysfunction is not resolved to date and comprises inflammation, barrier dysfunction and oxidative stress. Disease-associated reduction of tissue cystathionine-gamma-lyase (CSE) expression, an endogenous H2S-producing enzyme, is associated with oxidative stress, barrier dysfunction and organ injury. CSE-mediated cardio-protection has been suggested to be related the upregulation of oxytocin receptor (OTR). CSE can also mediate glucocorticoid receptor (GR) signaling, which is important for normal heart function. A sepsis-related loss of cardiac CSE expression associated with impaired organ function has been reported previously. The aim of this current post hoc study was to investigate the role of cardiac GR and OTR after polymicrobial sepsis in a clinically relevant, resuscitated, atherosclerotic porcine model. Anesthetized and instrumented FBM (Familial Hypercholesterolemia Bretoncelles Meishan) pigs with high fat diet-induced atherosclerosis underwent poly-microbial septic shock (n=8) or sham procedure (n=5), and subsequently received intensive care therapy with fluid and noradrenaline administration for 24 hours. Cardiac protein expression and mRNA levels were analyzed. Systemic troponin, a marker of cardiac injury, was significantly increased in septic animals in contrast to sham, whereas OTR and GR expression in septic hearts were reduced, along with a down-regulation of anti-inflammatory GR target genes and the antioxidant transcription factor NRF2. These results suggest a potential interplay between GR, CSE and OTR in sepsis-mediated oxidative stress, inflammation and cardiac dysfunction.